2022
DOI: 10.1155/2022/3665919
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy Analysis of Fast Rehabilitation Nursing on Pain Mitigation after Lumbar Discectomy and Bone Graft Fusion and Internal Fixation

Abstract: Objective. To investigate clinical efficacy analysis of fast rehabilitation nursing on pain mitigation after lumbar discectomy and bone graft fusion and internal fixation. Methods. A total of 60 patients with lumbar disc herniation who underwent lumbar discectomy and bone graft fusion and internal fixation in our hospital from January 2021 to December 2021 were randomized either into routine group (n = 30) or rehabilitation group (n = 30) via the random number table method. The patients in the routine group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A total of 40 studies [6–46] reported the effective rate of different treatment regimens, with a total of 3710 patients, including 1861 patients in the observation group and 1849 patients in the control group. Through subgroup meta-analysis, heterogeneity test showed I ² = 0%, indicating no heterogeneity among the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 40 studies [6–46] reported the effective rate of different treatment regimens, with a total of 3710 patients, including 1861 patients in the observation group and 1849 patients in the control group. Through subgroup meta-analysis, heterogeneity test showed I ² = 0%, indicating no heterogeneity among the studies.…”
Section: Resultsmentioning
confidence: 99%
“…9 studies [ 7 , 10 , 24 , 48 , 54 , 56 , 64 , 65 , 72 ] reported post-treatment ODI scores of 1344 patients in both groups, 627 patients in the observation group and 627 patients in the control group. After conducting subgroup meta-analysis, the heterogeneity test showed I ² = 95.7%, P < .00001, indicating significant heterogeneity among the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%